How euro area's monetary policy effects differ among its countries : Including findings about Finland - Rettinen, Roni (My University, 2025)
Significance of the common monetary policy of the euro area is emphasized especially in times of crises. It is one of the most important tools for price stabilization. The aim of this thesis is to study how monetary policy effects differ among euro countries, and how Finland is positioned in such classification. This thesis explores how the real economy variables such as output and employment react in different countries. Special attention is paid to the government bonds. Such questions are usually studied by different variants of vector autoregressions (VAR). This research follows the methodology of Altavilla et al. (2019) and Gertler & Karadi (2015), which is based on VAR and monetary policy surprises. Surprises are identified from the sudden price movements of selected bonds and indices during the European Central Bank's (ECB) press releases and conferences. Data sources are the EA-MPD database supported by ECB, and daily time series of selected countries' sovereign bonds. Effects of the monetary policy surprises on the bond yields and term premia are studied. Results show that such effects are persistent and quite homogenic among countries. As expected, bonds of stronger economy countries, such as Germany and France, behave most predictably. Finland is positioned closely to these countries in most cases. Term premium is found to be dependent on the bond yield level. As a conclusion, the euro area countries' economies react to the monetary policy measures in a similar way, although some differences can be detected from time to time. Same holds for the government bonds, which can be classified according to the country-specific risk as more and less predictable. Business cycles synchronization has grown, but it usually decreases in crisis times and increases during periods of economic growth. This can be considered as a positive outcome in terms of the monetary policy efficiency.

Euroalueen yhteisen rahapolitiikan merkitys korostuu erityisesti kriisien aikana. Tämä on yksi tärkeimmistä keinoista hintatason vakauttamiseen. Tutkielman tarkoitus on selvittää, miten rahapolitiikan vaikutus eroaa maiden välillä, ja mihin Suomi sijoittuu sellaisessa tarkastelussa. Tutkielmassa kartoitetaan, miten reaalimuuttujat, kuten tuotanto ja työllisyys, reagoivat eri maissa. Huomiota kiinnitetään myös valtioiden velkakirjoihin. Sellaisia kysymyksiä tutkitaan yleensä erilaisilla vektoriautoregression (VAR) variaatioilla. Tämä tutkielma seuraa Altavillan ym. (2019) ja Gertlerin & Karadin (2015) metodologiaa, joka perustuu VAR-analyysiin ja rahapolitiikan yllätyksiin. Yllätyksiä identifioidaan tiettyjen velkakirjojen hintojen ja indeksien äkillisistä muutoksista Euroopan keskuspankin (EKP) tiedotustilaisuuksien aikana. Aineistona on EKP:n ylläpitämä EA-MPD-tietokanta, ja lisäksi valittujen valtioiden velkakirjojen tuottojen päivittäiset aikasarjat. Tutkitaan rahapolitiikan yllätysten vaikutuksia velkakirjojen tuottoihin ja myös niiden juoksuaikapreemioihin. Tulokset osoittavat, että yllätysten vaikutus velkakirjojen tuottoihin on pitkään kestävä ja melko homogeeninen maiden välillä. Odotetusti vahvempien talouksien, kuten Saksan ja Ranskan, velkakirjat käyttäytyvät ennalta arvattavammin. Suomi sijoittuu edellä mainittujen maiden lähelle. Juoksuaikapreemio osoittautuu riippuvan tuoton tasosta. Johtopäätöksenä voidaan todeta, että euromaiden taloudet reagoivat rahapolitiikan toimenpiteisin melko samantyyppisesti, vaikka eroavaisuuksia myös havaitaan jonkin verran. Sama pätee myös valtioiden velkakirjoihin, jotka voidaan luokitella maakohtaisen riskin mukaan enemmän ja vähemmän ennustettaviin. Suhdanteiden synkronointi on kasvanut, mutta se yleensä heikkenee kriisien aikana ja vahvistuu noususuhdanteissa. Sitä täytyy pitää positiivisena asiana rahapolitiikan tehokkuuden näkökulmasta.
Keywords: monetary policy, VAR, bond, European Central Bank, euro area